Analisis Semiotika Pesan Sindiran Kepada Birokrasi Pemerintahan Dalam Film Animasi Zootopia - Rizki Ahmalina Putra (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2022)
This study aims to analyze the message in the animated film Zootopia. Film as a product of mass media, contains a message to be conveyed by the maker. However, not a few film lovers are immersed in the story and visuals presented, thus ignoring the message that is full of meaning in it. For this reason, this study was conducted to analyze the messages contained in this film. This study uses a qualitative method, with a semiotic analysis approach. The results of the study indicate that this film contains a satirical message against the government bureaucracy.